A questionnaire survey on using clinical practice guidelines - HIRAWA, Mariko (Igaku toshokan. Medical libraries, 2005)
Toho University Medical Media Center carried out a web survey of users of its clinical practice guidelines webpages over 295 days. There were 965 responses: 721 (74%) were from physicians from a wide range of disciplines. 367 stated which guidelines they used: the most popular were neurology and cardiovascular. 161 physicians said they used guidelines for routine medical practice. Of the 33 members of the public who responded, 17 said they used guidelines for information on personal or family illnesses. Original article in Japanese. (Original abstract - amended)